K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

22 tháng 2 2018

a)\(\left(-2\right)^3.3\)

\(=\left(-8\right).3=-24\)

b)\(2^2.\left(-3\right)^2.5\)

\(=4.9.5\)

\(=36.5\)

\(=180\)

22 tháng 2 2018

( -2 )3. 3 

= [ ( -2 ) . ( -2 ) . ( -2 ) ] . 3

= ( -8 ) . 3

= -24

22 .  ( -3 ) 2 . 5 

= [ 2 . 2 ] . [ ( -3 ) . ( -3 ) ] . 5

= 4 . 9 . 5

= 36 . 5

= 180

Chúc bn học tốt!

29 tháng 11 2015

A=1-3+3^2-3^3+3^4-3^5+...+3^38-3^39+3^100

3A=3-3^2+3^3-3^4+3^5-3^6+...+3^99-3^100+3^101

3A+A=3-3^2+3^3-3^4+3^5-3^6+...+3^99-3^100+3^101+1-3+3^2-3^3+3^4-3^5+...+3^98-3^99+3^100

4A=3^101+1

A=(3^101+1)/4

30 tháng 5 2016

Ta có: \(\frac{\left(-2\right)^3.3^3.5^3.7.8}{3.2^4.5^3.14}=\frac{\left(-2\right)^3.3.3^2.5^3.7.2^3}{3.2.2^3.5^3.2.7}=\frac{-\left(2\right)^6.3^2}{2^2}=\frac{\left(-64\right).9}{4}=-\frac{576}{4}\) \(=-144\)

30 tháng 5 2016

= - 144 nha♡♡♡

15 tháng 8 2015

A = 1 + (1+ 1).2 + (1 + 2).3 + (1+3).4 + ...+ (1 + n-1). n

A = 1 + (2+1.2) + (3+ 2.3) + (4 + 3.4) + ....+ ( n + (n -1).n)

A = (1+ 2  + 3 + 4 + ...+ n) + (1.2 + 2.3 + 3.4 + .....+ (n-1).n)

Tính B = 1+ 2+ 3 + ...+ n = (n +1).n/ 2

C = 1.2+ 2.3 + 3.4 + ...+ (n-1).n

=> 3.C = 1.2.3 + 2.3.3 + 3.4.3 + ...+ (n-1).n.3

3C = 1.2.3 + 2.3. (4 -1) + 3.4.(5 - 2) + ... + (n -1).n [(n+ 1) - (n -2)]

3C = [1.2.3 + 2.3.4 + ....+ (n-1).n.(n +1)] - (1.2.3 + 2.3.4 + ... + (n-2)(n -1).n)

3C = (n -1).n (n +1) => C = (n -1).n.(n +1)/ 3

Vậy A = (n +1).n/ 2 + (n -1).n(n +1)/3

14 tháng 8 2015

A = 1 + (1+ 1).2 + (1 + 2).3 + (1+3).4 + ...+ (1 + n-1). n

A = 1 + (2+1.2) + (3+ 2.3) + (4 + 3.4) + ....+ ( n + (n -1).n)

A = (1+ 2  + 3 + 4 + ...+ n) + (1.2 + 2.3 + 3.4 + .....+ (n-1).n)

Tính B = 1+ 2+ 3 + ...+ n = (n +1).n/ 2

C = 1.2+ 2.3 + 3.4 + ...+ (n-1).n

=> 3.C = 1.2.3 + 2.3.3 + 3.4.3 + ...+ (n-1).n.3

3C = 1.2.3 + 2.3. (4 -1) + 3.4.(5 - 2) + ... + (n -1).n [(n+ 1) - (n -2)]

3C = [1.2.3 + 2.3.4 + ....+ (n-1).n.(n +1)] - (1.2.3 + 2.3.4 + ... + (n-2)(n -1).n)

3C = (n -1).n (n +1) => C = (n -1).n.(n +1)/ 3

Vậy A = (n +1).n/ 2 + (n -1).n(n +1)/3

bài làm

A = 1 + (1+ 1).2 + (1 + 2).3 + (1+3).4 + ...+ (1 + n-1). n

A = 1 + (2+1.2) + (3+ 2.3) + (4 + 3.4) + ....+ ( n + (n -1).n)

A = (1+ 2  + 3 + 4 + ...+ n) + (1.2 + 2.3 + 3.4 + .....+ (n-1).n)

B = 1+ 2+ 3 + ...+ n = (n +1).n/ 2

C = 1.2+ 2.3 + 3.4 + ...+ (n-1).n

=> 3.C = 1.2.3 + 2.3.3 + 3.4.3 + ...+ (n-1).n.3

3C = 1.2.3 + 2.3. (4 -1) + 3.4.(5 - 2) + ... + (n -1).n [(n+ 1) - (n -2)]

3C = [1.2.3 + 2.3.4 + ....+ (n-1).n.(n +1)] - (1.2.3 + 2.3.4 + ... + (n-2)(n -1).n)

3C = (n -1).n (n +1)

=> C = (n -1).n.(n +1)/ 3

Vậy............

hok tốt